Theoretical and experimental analysis on the small punch creep deformation of Incoloy800H. (February 2018) - Yang, Sisheng; Ling, Xiang
Abstract: The small punch creep deformation behavior estimation of Incoloy800H was performed theoretically and experimentally in this study. The results indicate that three creep stages of the small punch test are similar to that of the conventional creep tests. Considering the deformation characteristics and geometry form, an obvious initial elastic-plastic deformation is presented and the primary creep stage is proven to be nonnegligible in the small punch test. Both the three-point bending model and the modified geometric model were proposed. It indicates that creep strain is proportional to small punch deflection in the primary and steady creep stages. Meanwhile, membrane stretching model was modified and a constant stress phase during deformation was found. The results indicate that small punch character parameters are capable to replace traditional creep data in the creep curve analysis of Incoloy800H. Thus, the creep curves with three deformation phases were analyzed and predicted by both of the modified Norton-Bailey model and modified theat model. Finally, the primary, steady and tertiary creep stages were described, and the creep life prediction of Incoloy800H was realized. Highlights: Small punch creep deformation behavior of Incoloy800H was estimated. Three-point bending model and modified geometric model were proposed. A modified membrane stretch model was proposed to estimate the constant stress phase. Creep curve was predicted by modified Norton-Bailey model and modified theat model. The primary, steady and tertiary creep stages were described and predicted.